Orbital and rotational dynamics of solar power satellites in geosynchronous orbits - McNally, Ian J (University of Glasgow, 2018)
Designs for geostationary (GEO) solar power satellites (SPS) are extremely large in scale, more than one order of magnitude larger than the International Space Station. In this thesis a detailed study of the orbit dynamics of SPS is performed. Analytical equations, derived by the process of averaging of the SPS equations of motion, are used to determine the long-term orbital evolution. Previous SPS studies have simply assumed a GEO as the operational orbit, and then designed control systems for maintaining the orbit within acceptable nominal values. It is found that an alternative SPS orbital location known as the geosynchronous Laplace plane orbit (GLPO) is superior to GEO in many aspects. An SPS in GLPO requires virtually no fuel to maintain its orbit, minimises the risk of debris creation at geosynchronous altitude, and is extremely robust operationally, i.e. loss of control is inconsequential. The GLPO SPS requires approximately 10^5 kg less fuel per year compared to a GEO SPS while providing near equivalent power delivery. Although savings in orbit control are achieved, depending on the mass distribution of the SPS, attitude control costs may be incurred by placing an SPS in GLPO. Consideration of the attitude dynamics of SPS has motivated the development of a model for the rotational dynamics of a body which includes energy dissipation and the effects of external torques. Multiple spring-damper masses are used to provide a mechanism for energy dissipation. This rotational dynamics model is used to assess the naturally stable attitude configurations of a SPS design in geosynchronous orbit subject to gravity gradient torque. It is found that for a large planar array, a dynamically stable configuration requiring nominal orbit-attitude control is possible. This involves rotating around the maximum axis of inertia at the orbit rate, with the minimal axis aligned in the radial direction. It will be shown that a SPS in this configuration while in GLPO requires virtually no orbit or attitude control. The most significant result of the research in this thesis is proving that a SPS can operate in GLPO with nominal orbit control and yet still deliver almost equivalent power to the Earth’s surface as the same SPS would in a controlled GEO.